The merchant of death - MacHale, D. J. (New York : Aladdin Paperbacks, 2002)
Fourteen-year-old Bobby Pendragon, having learned he is a Traveler--someone who can ride "flumes" through time and space, is soon off to the alternative dimension of Denduron where he teams up with Loor, a girl his age from the warrior-territory of Zadaa, in an attempt to save the gentle Milago people from slavery.
5.4
5-8
Keywords: Space and time -- Fiction; Life on other planets -- Fiction; Time travel -- Fiction; Mystery and detective stories; Adventure and adventurers -- Fiction; Space and time -- Fiction; Life on other planets -- Fiction; Time travel -- Fiction; Mystery fiction; Adventure fiction